Aksiologi Islam dan Kesadaran Etis Siswa SD terhadap Fenomena Cyberbullying - Novi Wibowo (Jurnal Konseling dan Psikologi Indonesia, 2026)
This study aims to describe the role of Islamic axiology in fostering elementary students’ ethical awareness of cyberbullying phenomena. The research subjects were 18 sixth-grade students at SD Negeri 2 Parijatah Kulon in the 2025/2026 academic year, consisting of 12 boys and 6 girls. The research employed a descriptive qualitative approach through observation, interviews, and documentation. The findings indicate that Islamic axiological values, particularly Islamic communication ethics such as qaulan karima, qaulan ma’rufa, and qaulan layyina, foster students’ awareness to interact more responsibly in digital spaces. This study confirms that Islamic Religious Education plays a strategic role in instilling ethical awareness of digital media use from an early age.